Clinical and Immunological Features of Human BCL10 Deficiency - Garcia-Solis, Blanca; Van Den Rym, Ana; Pérez-Caraballo, Jareb J.; Al–Ayoubi, Abdulwahab; Alazami, Anas M.; Lorenzo, Lazaro; Cubillos-Zapata, Carolina; López-Collazo, Eduardo; Pérez-Martínez, Antonio; Allende, Luis M.; Markle, Janet; Fernández-Arquero, Miguel; et al. (Frontiers in Immunology, 2021)
The CARD-BCL10-MALT1 (CBM) complex is critical for the proper assembly of human immune responses. The clinical and immunological consequences of deficiencies in some of its components such as CARD9, CARD11, and MALT1 have been elucidated in detail. However, the scarcity of BCL10 deficient patients prevented gaining that knowledge for this genetic disease. Only two patients with BCL10 deficiency have been reported to date. Here we describe in more depth an additional patient with autosomal recessive BCL10 complete deficiency caused by a nonsense mutation that leads to a loss of expression (K63X). Using mass cytometry coupled with unsupervised clustering and machine learning computational methods, we obtained a thorough characterization of the consequences of BCL10 deficiency in different populations of leukocytes. We showed that in addition to the almost absence of memory B and T cells reported before, this patient display a reduction in NK, gdT, Tregs, and TFH cells. The patient suffered from recurrent respiratory infections since early in life, and showed a family history of lethal severe infectious diseases. Fortunately, hematopoietic stem-cell transplantation (HSCT) cured her. Overall, this report highlights the importance of early genetic diagnosis for the management of BCL10 deficient patients and HSCT as the recommended treatment to cured this disease.